Changing environment of the Baltic Sea should be recognized in the future resource management activities - Jari Hänninen (Pan-Europan Institute, 2022)
As is well known, the political balance of the Baltic Sea has spent restless times during the last years mainly due to its strategic position between east and west. Since the 1980s, the rapidly changing situation has been a reality for the environmental condition of the sea as well. The reason for this has been the global climate change, which influences especially the exceptional characteristic of the Baltic Sea – the salinity content of the brackish seawater. The changing environment should be better recognized in the future management activities of the sea.